2022
DOI: 10.1038/s41598-022-09095-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a risk-score model for opioid overdose using a national claims database

Abstract: Opioid overdose can be serious adverse effects of opioid analgesics. Thus, several strategies to mitigate risk and reduce the harm of opioid overdose have been developed. However, despite a marked increase in opioid analgesic consumption in Korea, there have been no tools predicting the risk of opioid overdose in the Korean population. Using the national claims database of the Korean population, we identified patients who were incidentally prescribed non-injectable opioid analgesic (NIOA) at least once from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
3
5
0
Order By: Relevance
“…Considering this discrepancy in the identified categories, ED visits in Korea could be lower than those in the United States. This finding is in line with a previous study in Korea, which reported that the incidence of opioid overdoses in NIOA incident users (0.05%) was lower than that in previous studies (0.4–0.6%) [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…Considering this discrepancy in the identified categories, ED visits in Korea could be lower than those in the United States. This finding is in line with a previous study in Korea, which reported that the incidence of opioid overdoses in NIOA incident users (0.05%) was lower than that in previous studies (0.4–0.6%) [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…Chronic opioid use is also linked to the development of opioid use disorder and abuse 44 . Our previous study also confirmed that the number of NIOA prescriptions was the strongest predictor of opioid overdose 23 . By facilitating the early identification of patients at an elevated risk of transitioning to chronic opioid use, our risk score prediction model enables individualized pain management strategies and informed discussions with patients.…”
Section: Discussionsupporting
confidence: 70%
“…44 Our previous study also confirmed that the number of NIOA prescriptions was the strongest predictor of opioid overdose. 23 By facilitating the early identification of patients at an elevated risk of transitioning to chronic opioid use, our risk score prediction model enables individualized pain management strategies and informed discussions with patients. Consequently, it may help mitigate chronic opioid use and its associated adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations